Lattice Boltzmann simulation of melting heat transfer in a composite phase change material. (25th July 2020) - Han, Qun; Wang, He; Yu, Cheng; Zhang, Chengbin
Highlights: Composite PCM is applied to enhance the thermal energy storage performance. Melting behavior of composite PCM is studied by lattice Boltzmann method. Solid-liquid interface and dynamic temperature evolution are analyzed. Fully dispersed metal particles enhance the melting performance of PCM. Metal particles are suggested to diffuse in identical direction of heat flows. Abstract: Thermal performance enhancement of the phase change material (PCM) is of particular significance to the energy storage applications. The composite PCM with metal particles is introduced here for maximizing the thermal performance. Based on the description of a composite PCM by the QSGS method, a lattice Boltzmann model of the melting composite PCM was developed and numerically solved. The melting front evolution and transient temperature response in the composite PCM are analyzed and compared to the pure PCM. Furthermore, the effects of the dispersity, volume fraction, and diffusion direction of the metal particles on the melting performance of composite PCMs are comprehensively analyzed. The results indicate that the presence of metal particles benefits the thermal performance enhancement of PCMs. The melting evolution and the heat transfer in the composite PCM are much quicker due to the enhanced thermal conduction. Besides, the melting front morphology maintains an approximate line during the whole melting process arising from the natural convection suppression. For maximizing the melting heat transport, the metal particles in the composite PCM are recommended to present a larger dispersity, and their diffusion direction is suggested to be in the same direction as the heat flow. Interestingly, even though the volume fraction of the metal particles is identical, the melting performance of composite PCM is also relevant to the dispersity and diffusion direction of the metal particles.